Dissection of Floral Organ Development and Sterility in Sorghum Bicolor - (:unkn) unknown (My University, 2019)
Sorghum bicolor is a drought resistant cereal grain commonly grown for use in food, feed, fiber, and fuel production. Due to its versatility and modest sized genome it is poised to become an increasingly important research organism within the C4 plants. Sorghum produces spikelet pairs with one fertile sessile spikelet and one to two sterile pedicellate spikelets. One major area of interest in sorghum production is maximizing seed yield. While the importance of the grain is obvious there are several large gaps in the study of sorghum that prevent researchers and growers from maximum productivity. The first gap is that limited study has looked at the effects of heat stress on early anther development, the effects of varied heat stress durations and the effects of heat stress at 42°C on seed yield. Another key gap in sorghum study is the lack of a complete floral developmental series from primordia to anthesis. Building on this idea, no study has determined why over half of the spikelets produced in sorghum are sterile at maturity. The final gap is in the study of male fertility and anther development. Prior to this study a complete anther series from origin to dehiscence was not available, no male sterile mutants were fully characterized, and few sorghum mutants made available for hybrid breeding efforts. We demonstrated that heat stress applied at booting stage, where spikelets are only surrounded by a bulged leaf sheath, had devastating effects on yield. Specifically, loss of male fertility resulted in loss of grain yield. In addition, limited effects were observed on vegetative development. Additionally, a complete floral developmental series was formed, which highlighted key developmental stages that were targeted for RNA-seq study. Transcriptomic analysis demonstrated altered expression of TEOSINTE BRANCHED 1, CYCLOIDEA, PCF1 transcription factor genes, MADS-box genes and phytohormone genes which are hypothesized to result in pedicellate sterility. Finally, a complete anther developmental series was constructed for the WT and ms8 mutant and initial characterization of Sbtdr mutant development was completed. This work identified two important candidates for hybrid breeding efforts in sorghum. Overall these efforts provide important resources to fill developmental knowledge gaps in sorghum and further seed yield improvement research. From this work specific pathways have been identified for future study that could vastly improve seed yield.
Keywords: Fertility; Floral development; RNA-seq; Sorghum bicolor; Sterility; Yield